2017
DOI: 10.1371/journal.pone.0172171
|View full text |Cite
|
Sign up to set email alerts
|

High-quality RNA extraction from the sea urchin Paracentrotus lividus embryos

Abstract: The sea urchin Paracentrotus lividus (Lamarck, 1816) is a keystone herbivore in the Mediterranean Sea due to its ability to transform macroalgal-dominated communities into barren areas characterized by increased cover of bare substrates and encrusting coralline algae, reduced biodiversity and altered ecosystem functions. P. lividus is also an excellent animal model for toxicology, physiology and biology investigations having been used for more than a century as a model for embryological studies with synchronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…It has shown that the use of sea urchin shells confers certain beneficial advantages, including antioxidant and pharmaceutical effects (Shankarlal et al, 2011). The sea urchin, Paracentrotus lividus (Dincer and Cakli, 2007) is a keystone herbivore in the Mediterranean Sea (Ruocco et al, 2017). It has special substances, such as quinonoid pigments which called echinochromes (Mohamed et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has shown that the use of sea urchin shells confers certain beneficial advantages, including antioxidant and pharmaceutical effects (Shankarlal et al, 2011). The sea urchin, Paracentrotus lividus (Dincer and Cakli, 2007) is a keystone herbivore in the Mediterranean Sea (Ruocco et al, 2017). It has special substances, such as quinonoid pigments which called echinochromes (Mohamed et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The application of RNA‐Seq in embryos is limited by the low RNA content of a single pre‐hatching bovine embryo (200–2,300 pg) depending on the stage of the development (Gilbert et al., ). To ensure sufficient quantity and integrity of RNA for RNA‐Seq, we used RNeasy ® Micro Kit (Ruocco et al., ) to extract RNA from yak embryos and Smart‐seq2 (Picelli et al., ) to generate sequencing libraries from embryos. In this way, we successfully provide the first comprehensive description of gene activities during in vitro yak embryonic development in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from pooled embryos of each stage using RNeasy ® Micro Kit (Qiagen, Austin, TX, US) as previously described by Ruocco et al (2017). Full-length single-cell RNAseq libraries were prepared using the Smart-seq2 protocol (Picelli et al, 2013) with minor modifications.…”
Section: Library Preparation and Sequencingmentioning
confidence: 99%
“…Total RNA was extracted using Aurum ™ Total RNA Mini Kit (Bio-Rad, Hercules, CA, USA), according to the manufacturer’s instructions 53 for RNA-seq experiments. Total RNA was extracted using RNAqueous Micro Kit (Ambion from Life Technologies), according to the manufacturer’s instructions for Real Time qPCR experiments 53 . Samples were stored at −80 °C.…”
Section: Methodsmentioning
confidence: 99%